An economic case for a cardiovascular polypill? A cost analysis of the Kanyini GAP trial. Issue 11 (15th December 2014) - Laba, Tracey‐Lea; Hayes, Alison; Lo, Serigne; Peiris, David P; Usherwood, Tim; Hillis, Graham S; Rafter, Natasha; Reid, Christopher M; Tonkin, Andrew M; Webster, Ruth; Neal, Bruce C; Cass, Alan; et al.
Abstract: Objective: To measure the costs of a polypill strategy and compare them with those of usual care in people with established cardiovascular disease (CVD) or at similarly high cardiovascular risk. Design: A within‐trial cost analysis of polypill‐based care versus usual care with separate medications, using data from the Kanyini Guidelines Adherence with the Polypill (GAP) trial and linked health service and medication administrative claims data. Participants: Kanyini GAP participants who consented to Australian Medicare record access. Main outcome measure s : Mean health service and pharmaceutical expenditure per patient per year, estimated with generalised linear models. Costs during the trial (randomisation January 2010 – May 2012, median follow‐up 19 months, maximum follow‐up 36 months) were inflated to 2012 costs. Results: Our analysis showed a statistically significantly lower mean pharmaceutical expenditure of $989 (95% CI, $648–$1331) per patient per year in the polypill arm compared with usual care ( P   < 0.001; adjusted, excluding polypill cost). No significant difference was shown in health service expenditure. Conclusions: This study provides evidence of significant cost savings to the taxpayer and Australian Government through the introduction of a CVD polypill strategy. The savings will be less now than during the trial due to subsequent reductions in the costs of usual care. Nonetheless, given the prevalence of CVD in Australia, the introduction of this polypill could increase considerably the efficiency of health care expenditure in Australia. Trial registration: Australian New Zealand Clinical Trials Registry ACTRN126080005833347.